The Influence of the Play–Teach–Play Model on Students’ Freestyle Swimming Skills (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of the Play–Teach–Play (PTP) model on Students’ Freestyle Swimming Skills. The research method used was an experimental approach with a One Group Pretest pretest-posttest design, involving 32 third-grade students from SDN Bagendit 1 as research samples selected through purposive sampling. The instrument used was an observation sheet of basic aquatic skills, which included aspects of body position, leg movement, arm movement, and breathing. The results showed a significant improvement in freestyle swimming skills after the implementation of the Play–Teach–Play model. The Paired Sample t-test yielded a significance value of 0.000 (p < 0.05), with the mean score increasing from 11.19 (pretest) to 18.16 (posttest), resulting in a gain of 6.97. This finding proves that the Play–Teach–Play model is effective in improving students’ freestyle swimming skills through the stages of play, technical instruction, and reapplication in the form of enjoyable games. It can be concluded that the Play–Teach–Play model has a significant effect on enhancing students’ freestyle swimming skills.